The Impact of Embezzlement of Bank Indonesia Deposit Cash in Maluku and the Implications for Banking Security - Salmon, Harly Cliford Jonas (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: One of the most common criminal offenses in the banking sector is falsification of records, particularly in the provision of credit facilities. Falsification of records refers to the act of creating or manipulating data and information that do not reflect reality to gain unlawful advantages. The case of misappropriation of Bank Indonesia’s entrusted funds faced by the Regional Development Bank of Maluku and North Maluku, involving an outsourced employee, serves as a concrete example of how banking crimes can have widespread effects and negative impactsPurposes of the Research:  To analyze the legal impact and implications of the misappropriation of Bank Indonesia’s entrusted funds in Maluku on the banking sector.Methods of the Research: This study employs a normative legal research method, primarily utilizing library research as the main data source. It adopts a conceptual approach, gathering data from various literature sources. Legal materials are collected from secondary legal sources, then processed and analyzed qualitatively.Findings of the Research: What is new in this Research that may benefit readers and how it is advancing the existing knowledge or creating new knowledge in this subject. It is at the heart of a research report because a finding is what the reader is actually looking for. The findings component does not have to present all the things that are found in the research, it is presented that the findings are relevant to the nature of this research. For example: The results show that or The findings of this study prove that businesses that reached their dominant position before the recession had a significant advantage over small businesses. However, they cannot be compelled to act on the same basis for very long, which is why a more US-like model would be useful for controlling some of these business behaviors.